Disturbance of the Glutamate-Glutamine Cycle, Secondary to Hepatic Damage, Compromises Memory Function - Limón, Ilhuicamina Daniel; Angulo-Cruz, Isael; Sánchez-Abdon, Lesli; Patricio-Martínez, Aleidy (Frontiers in Neuroscience, 2021)
Glutamate fulfils many vital functions both at a peripheral level and in the central nervous system (CNS). However, hyperammonemia and hepatic failure induce alterations in glutamatergic neurotransmission, which may be the main cause of hepatic encephalopathy (HE), an imbalance which may explain damage to both learning and memory. Cognitive and motor alterations in hyperammonemia may be caused by a deregulation of the glutamate-glutamine cycle, particularly in astrocytes, due to the blocking of the glutamate excitatory amino-acid transporters 1 and 2 (EAAT1, EAAT2). Excess extracellular glutamate triggers mechanisms involving astrocyte-mediated inflammation, including the release of Ca2+-dependent glutamate from astrocytes, the appearance of excitotoxicity, the formation of reactive oxygen species (ROS), and cell damage. Glutamate re-uptake not only prevents excitotoxicity, but also acts as a vital component in synaptic plasticity and function. The present review outlines the evidence of the relationship between hepatic damage, such as that occurring in HE and hyperammonemia, and changes in glutamine synthetase function, which increase glutamate concentrations in the CNS. These conditions produce dysfunction in neuronal communication. The present review also includes data indicating that hyperammonemia is related to the release of a high level of pro-inflammatory factors, such as interleukin-6, by astrocytes. This neuroinflammatory condition alters the function of the membrane receptors, such as N-methyl-d-aspartate (NMDA), (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) AMPA, and γ-aminobutyric acid (GABA), thus affecting learning and spatial memory. Data indicates that learning and spatial memory, as well as discriminatory or other information acquisition processes in the CNS, are damaged by the appearance of hyperammonemia and, moreover, are associated with a reduction in the production of cyclic guanosine monophosphate (cGMP). Therefore, increased levels of pharmacologically-controlled cGMP may be used as a therapeutic tool for improving learning and memory in patients with HE, hyperammonemia, cerebral oedema, or reduced intellectual capacity.